2021
DOI: 10.7150/jca.62131
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Diffusion MRI for differentiating Benign and Malignant Nonfatty Musculoskeletal Soft Tissue Tumors: A Systematic Review and Meta-analysis

Abstract: Objective: To evaluate the diagnostic performance of standard diffusion-weighted imaging (DWI), intravoxel incoherent motion (IVIM), and diffusion kurtosis imaging (DKI), for differentiating benign and malignant soft tissue tumors (STTs). Materials and methods: A thorough search was carried out to identify suitable studies published up to September 2020. The quality of the studies involved was evaluated using Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…DWI and ADC maps were used in human medicine helping distinguish orbital tumour and inflammation, or differentiate benign and malignant soft tissue tumours. Increased cell density and decreased extracellular space in malignant tumours will hinder the movement of water molecules and therefore have decreased ADC values (Wang et al., 2021). Also, the tumour stroma produced by activated fibroblasts was found to be inversely correlated to ADC value (Hauge et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…DWI and ADC maps were used in human medicine helping distinguish orbital tumour and inflammation, or differentiate benign and malignant soft tissue tumours. Increased cell density and decreased extracellular space in malignant tumours will hinder the movement of water molecules and therefore have decreased ADC values (Wang et al., 2021). Also, the tumour stroma produced by activated fibroblasts was found to be inversely correlated to ADC value (Hauge et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…32,35 There is consensus, however, that lower ADC values are more likely to indicate malignancy. [36][37][38][39][40][41] DWI with ADC mapping offers value for MSK tumor characterization in three particular scenarios: First, showing significantly lower ADC values for malignant compared with benign lesions, DWI enhances the diagnostic accuracy of conventional MRI of soft tissue masses with indeterminate tumor characteristics by conventional imaging and clinical features. [42][43][44] Moreover, Del Grande et al reported a comparable diagnostic performance between noncontrast MRI protocols with DWI and contrast-enhanced protocols for indeterminate soft tissue masses.…”
Section: Functional Sequencesmentioning
confidence: 99%
“…[6][7][8][9] DKI was first used to track changes in gray matter in the brain but has since been extensively utilized in the research on malignancies of the nervous system, digestive system, breast, prostate, and other disorders of the musculoskeletal system. [10][11][12][13][14] The equation 7 for DKI analysis of the non-Gaussian diffusivity of water is as follows:…”
Section: The Principle Of Dki and Related Parametersmentioning
confidence: 99%
“…In addition to the monoexponential model, DKI can describe other fitted diffusion data models, such as the biexponential model which distinguishes between the quick and slow diffusion rate of water molecules, and the stretched‐exponential model which categorizes water diffusion into multiple Gaussian intervals through widely distributed diffusivities, more accurately reflecting the degree of diffusion restriction and inhomogeneity of water molecules 6–9 . DKI was first used to track changes in gray matter in the brain but has since been extensively utilized in the research on malignancies of the nervous system, digestive system, breast, prostate, and other disorders of the musculoskeletal system 10–14 …”
Section: The Principle Of Dki and Related Parametersmentioning
confidence: 99%